2023
DOI: 10.7759/cureus.33687
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Self-Care Methods for Acute Dental Pain Among Adults During COVID-19 Dissemination and the Implementation of Teledentistry in Makkah, Saudi Arabia: A Cross-Sectional Study

Abstract: Aim: This cross-sectional study aims to explore the prevalence of acute dental pain, different self-care methods done by adults to manage this pain, and the utilization of teledental platforms during the COVID-19 pandemic lockdown period. The study was conducted in Makkah, Saudi Arabia.Methods: A total of 727 participants answered the study questionnaire, which was distributed as an online survey on different social media platforms. The modified dental pain screening questionnaire (M-DePaQ) was used to obtain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…In contrast, the study conducted by Jarwan et al [ 24 ] found that 47.9% of respondents had moderate-to-severe pain, while 45% were affected by sleep disturbances. Perhaps the age and severity of the disease of our study participants are the main reasons for the significant difference in pain perception.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In contrast, the study conducted by Jarwan et al [ 24 ] found that 47.9% of respondents had moderate-to-severe pain, while 45% were affected by sleep disturbances. Perhaps the age and severity of the disease of our study participants are the main reasons for the significant difference in pain perception.…”
Section: Discussionmentioning
confidence: 84%
“…In Kosovo, participants expressed relatively high confidence ( n = 36, 65.5%) in their health system's ability to diagnose the virus. In contrast, results from participants in Makkah, Saudi Arabia (2023) [ 24 ] showed a significantly low utilization rate of 10% for the diagnostic capabilities of the health system. This discrepancy could be due to education, cultural beliefs, health insurance, and income.…”
Section: Discussionmentioning
confidence: 99%
“…These include varied levels of awareness and acceptance among the populace and dental professionals alike. Although some studies underscore the efficacy of digital platforms in dental health education and the promising role of teledentistry in clinical settings [4,5], concerns about diagnostic accuracy, cost implications, and data security loom large [6,7].…”
Section: Introductionmentioning
confidence: 99%